Multi‐hop medium access control protocol for low energy critical infrastructure monitoring networks using wake‐up radio. (19th December 2012) - Ullah, Niamat; Chowdhury, M. Sanaullah; Khan, Pervez; Kwak, Kyung Sup
SUMMARY The IEEE 802.15.4K Task Group was formed recently to address the low energy critical infrastructure monitoring networks. The aim is to collect scheduled and event data from a large number of non‐mains powered endpoints that are widely dispersed. The application requirements include reliable data transfer, energy efficiency, and long deployment lifetime. To meet the low energy critical infrastructure monitoring network requirements, we propose a multihop medium access control protocol where the scheduled or event data are routed to the coordinator through the cluster heads. The power consumption of the cluster heads is critical as they use more power than the normal endpoints. Our protocol uses the wake‐up radio approach from cluster head to cluster head communication and an efficient guaranteed time slots allocation scheme to minimize the power consumption of the cluster heads. We derive analytical expressions for the average power consumption of cluster heads as well as ordinary endpoints. The results show that our proposed protocol outperforms the IEEE 802.15.4 MAC and SCP MAC in terms of power consumption. High power efficiency is achieved in both the cluster heads and normal endpoints. Copyright © 2012 John Wiley & Sons, Ltd.